ORIENTASI MADRASAH DAN PENGEMBANGAN SUMBER DAYA MANUSIA - Yasin, A. Fatah (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
For educational purposes can be achieved, then education should be managed by a professional educational institutions with good management and by staff who have high work motivation. To be able to answer the challenges of the future of the madrasa institution must have a human resources ready to face a future full of risks. Human Resource Management in Islamic educational institutions (Madrasah) toward the quality, is a must in order to improve the quality of education in madrasas. To be able to build a system of Islamic education (madrasah) of quality, the main key is to have skilled human resources (quality). To be able to have a reliable human resources, the madrasas must implement measures or strategies in managing and developing human resources degan good.